Organizational culture and the impact towards job satisfaction and the efficiency among staff in Teknik Janakuasa Sdn Bhd / Julaiha Shamsuri (Faculty of Business Management, 2007)
Recently, job satisfactions among the employee become the most crucial subject in implementing the organization progress. Due to that, this research is conduct to carry out the organizational culture and the impact towards job satisfaction and the efficiency among staff in Teknik Janakuasa Sdn. Bhd. The pervasiveness of an organization's culture requires that management recognize the underlying dimensions of their corporate culture and its impact on employee-related variables such as satisfaction, commitment, cohesion, strategy implementation, performance, among others. Organizational culture is the pattern of shared values and beliefs that helps individuals to understand the way the organizational functions and so provides them with norms for behavior in the organization. This research examines the relationship between types of organizational culture and the job satisfaction in Teknik Janakuasa Sdn. Bhd. Chapter one consist of introduction and background of the research, chapter two consist of literature review, chapter three research methodology and design, chapter four data analysis and interpretation of data and chapter five conclusion and recommendations.